2013
DOI: 10.1186/1471-2458-13-149
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a smoking cessation program in a population of adolescent smokers in vocational schools: a public health evaluative controlled study

Abstract: BackgroundTo evaluate the public health efficacy of a community-based smoking cessation program (TABADO) among vocational school trainees (15 to 20 years old).MethodsThis prospective, controlled, quasi-experimental study was conducted in eight vocational training centres (VTC) in France. The intervention group underwent the TABADO program, which included a general information session for all students and small-group sessions plus individual counselling and nicotine therapy, if needed, for volunteers in an enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
0
24
0
4
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among these, six non-systematic literature and policy reviews reported increasing policy interest in health improvement interventions targeting young people within FE settings, but noted the absence of any evidence regarding appropriate or effective interventions in FE settings. 6,7,9,10,12,14 No examples of effective smoking prevention interventions delivered in this context were identified.…”
Section: Health Improvement In Further Education Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among these, six non-systematic literature and policy reviews reported increasing policy interest in health improvement interventions targeting young people within FE settings, but noted the absence of any evidence regarding appropriate or effective interventions in FE settings. 6,7,9,10,12,14 No examples of effective smoking prevention interventions delivered in this context were identified.…”
Section: Health Improvement In Further Education Settingsmentioning
confidence: 99%
“…17 One quasi-experimental study of a multicomponent intervention combining health education, counselling and nicotine therapy in French vocational colleges was found to be effective in supporting smoking cessation. 19 …”
Section: Health Improvement In Further Education Settingsmentioning
confidence: 99%
“…Selain itu, (Rosita, 2013) mengemukakan bahwa frekuensi merokok dan niat untuk berhenti merokok berhubungan dengan keberhasilan berhenti merokok. Perlu adanya (Minary, 2013) program intervensi berhenti merokok untuk membantu para perokok menghentikan perilaku tidak sehatnya. Intervensi yang dilakukan dalam penelitian Minary terbukti siknifikan menjadikan perokok menuju mantan perokok selama 12 bulan.…”
Section: Hasil Dan Pembahasanunclassified
“…Two other studies examined the use of CBT-based interventions in Korean [15] and French [16] adolescents. Chun, Bae and Min [15] evaluated CBT for smoking cessation among middle school smokers in South Korea; specifically, they compared a 6-session CBT intervention (n = 35) with a one hour education session (n = 45) using a pretest-posttest non-equivalence control group design.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Minary, Cambon, Martini, et al [16] conducted a quasi-experimental study of TABagisme chez les ADOlescents (TABADO) among adolescent smokers ( M age = 16.9 years; TABADO n = 386 [87.8% daily smokers; M age = 16.8 years]; control n = 557 [90.4% daily smokers; M age = 16.9 years]) in vocational training centers in France. In the TABADO condition, all participants received an information session about tobacco use and 18.1% of the TABADO participants chose to participate in the enhanced program (EP), which included four group CBT sessions and nicotine replacement therapy.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%